Exploring a Novel Approach: In vitro Cytotoxicity Study of Capecitabine Loaded Resealed Erythrocytes - Chivate, Anuradha Niranjan; Chivate, Niranjan Dattatray; Patil, Sudhir Sunil; Dhadde, Shivsharan Basavraj (Indian Journal of Pharmaceutical Education and Research)
Background: Conventional chemotherapy with Capecitabine is often associated with systemic toxicity, poor tumour selectivity, and suboptimal drug concentrations at tumour sites, limiting its therapeutic efficacy. Advanced drug delivery strategies are needed to enhance drug bioavailability while minimizing adverse effects. Objectives: This study investigates resealed erythrocytes as a novel drug delivery system for Capecitabine, aiming to improve targeted drug release, therapeutic efficacy, and biocompatibility in hepatocellular carcinoma treatment. Materials and Methods: Capecitabine was encapsulated within erythrocyte membranes to formulate Capecitabine-loaded resealed erythrocytes. The in vitro anticancer efficacy of the formulation was evaluated using MTT cytotoxicity assay and DAPI staining-based apoptosis analysis in HepG2 cells. Results: The MTT assay demonstrated that Capecitabine-loaded resealed erythrocytes exhibited enhanced cytotoxicity, with a lower IC50 value (206.6 μg/mL) compared to plain Capecitabine (315.4 μg/mL). DAPI staining further confirmed increased apoptotic activity, characterized by chromatin condensation and nuclear fragmentation. These findings suggest that erythrocyte carriers provide sustained and targeted drug release, improving the anticancer efficacy of Capecitabine. Conclusion: The encapsulation of Capecitabine within resealed erythrocytes presents a promising targeted drug delivery strategy for cancer therapy. This approach has the potential to enhance drug retention, reduce systemic toxicity, and improve therapeutic outcomes, warranting further investigation in preclinical and clinical settings.
Keywords: Cancer; Cytotoxicity; Capecitabine; Resealed erythrocytes; MTT assay; Apoptosis.